Population pharmacokinetics and dosing optimization of unbound teicoplanin in Chinese adult patients - Fu, Wen-Qian; Tian, Ting-Ting; Zhang, Min-Xin; Song, Hong-Tao; Zhang, Li-Li (Frontiers in Pharmacology, 2022)
Objectives: To develop a population pharmacokinetic (PopPK) model describing unbound teicoplanin concentrations in Chinese adult patients and perform Monte Carlo simulations to optimize the dosing regimens. Methods: The raw data for PopPK analysis in this study were collected from Chinese adult patients. A PopPK model of unbound teicoplanin was developed and Monte Carlo simulations were used to optimize the dosing regimens. The trough concentrations of unbound teicoplanin were targeted at 0.75 mg/L and 1.13 mg/L for most infection induced by Gram-positive bacteria and endocarditis or severe infections, respectively. Results: A total of 103 teicoplanin unbound concentrations were collected from 72 Chinese adult patients. A one-compartment pharmacokinetic model with first-order elimination was established. The typical values of clearance and the volume of distribution were 11.7 L/h and 811 L, respectively. The clearance and volume of distribution of unbound teicoplanin were positively correlated with estimated glomerular filtration rate (eGFR) and serum albumin concentrations, respectively. Dosing simulation results showed that standard dosing regimens were unable to meet the treatment needs of all patients, and the dosing regimen need optimize based on eGFR or serum albumin concentrations. The high eGFR and serum albumin concentration were associated with reduced probability of achieving target unbound trough concentrations. Conclusions: We successfully characterized the PK of unbound teicoplanin in Chinese adult patients. Importantly, we further highlight the importance of guiding dosing through unbound drugs. To achieve safe and effective treatment, the dosing regimens need to be adjusted according to eGFR and serum albumin concentrations.